People or Property Legal Contradictions, Climate Resettlement, and the View from Shifting Ground - Jerolleman, Alessandra; Marino, Elizabeth; Jessee, Nathan; Koslov, Liz; Comardelle, Chantel; Villarreal, Melissa; de Vries, Daniel; Manda, Simon (Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
This open access book explores the intersection of property law, relocation, and resettlement processes in the United States and among communities that grapple with migration as an adaptation strategy. As communities face the prospect of relocating because of rising seas, policy makers, disaster specialists, and community leaders are scrambling to understand what adaptation pathways are legally possible. While in its ideal application, law functions blindly and without variation, the authors find that legal contradictions come to bear on resettlement processes and place certain communities further in harm's way. This book will unearth these contradictions in order to understand why successful community-based resettlement has presented such a challenge to communities that are experiencing increasing land deterioration as a result of climate change. Alessandra Jerolleman is Associate Professor of Emergency Management, Jacksonville State University, USA. Elizabeth Marino is Associate Professor of Anthropology and Sustainability, Oregon State University, USA. Nathan Jessee is Postdoctoral Environmental Fellow at Princeton University's High Meadows Environmental Institute, USA. Liz Koslov is Assistant Professor in the Department of Urban Planning and the Institute of the Environment and Sustainability at UCLA, USA. Chantel Comardelle, Jean Charles Choctaw Nation, Tribal Secretary and Curator. Melissa Villarreal is a PhD candidate in Sociology at the University of Colorado (CU) Boulder, USA. Daniel de Vries is Associate Professor in Anthropology at the University of Amsterdam, the Netherlands. Simon Manda is Lecturer in International Development at the University of Leeds, UK.